Successful Approaches To Biomedical Maintenance Management And Their Implications For Nursing Practice (Journal of Namibian Studies : History Politics Culture, 2022)
Biomedical maintenance management is integral to ensuring the reliability and safety of medical equipment in healthcare settings. This article presents a series of case studies that illustrate successful approaches to biomedical maintenance management and their implications for nursing practice. Through real-life scenarios, key interventions, outcomes, and lessons learned are examined, highlighting the critical role of nurses in optimizing equipment performance and patient safety. The case studies encompass preventive maintenance programs, equipment recall management, emergency response protocols, and strategies for optimizing equipment utilization. Lessons gleaned from these cases underscore the importance of proactive maintenance planning, interdisciplinary collaboration, staff training, efficient recall management, emergency preparedness, and resource optimization. By integrating these lessons into their practice, nurses can contribute to enhanced patient care outcomes and healthcare system efficiency.